The dpsA gene of Streptomyces coelicolor: induction of expression from a single promoter in response to environmental stress or during development. - Paul D Facey; Beatrica Sevcikova; Renata Novakova; Matthew D Hitchings; Jason C Crack; Jan Kormanec; Paul J Dyson; Ricardo Del Sol (PLoS ONE)
The DpsA protein plays a dual role in Streptomyces coelicolor, both as part of the stress response and contributing to nucleoid condensation during sporulation. Promoter mapping experiments indicated that dpsA is transcribed from a single, sigB-like dependent promoter. Expression studies implicate SigH and SigB as the sigma factors responsible for dpsA expression while the contribution of other SigB-like factors is indirect by means of controlling sigH expression. The promoter is massively induced in response to osmotic stress, in part due to its sensitivity to changes in DNA supercoiling. In addition, we determined that WhiB is required for dpsA expression, particularly during development. Gel retardation experiments revealed direct interaction between apoWhiB and the dpsA promoter region, providing the first evidence for a direct WhiB target in S. coelicolor.